Detection and follow-up of cardiovascular disease and risk factors in the Southern Cone of Latin America: the CESCAS I study. Issue 1 (26th May 2011) - Rubinstein, Adolfo Luis; Irazola, Vilma Edith; Poggio, Rosana; Bazzano, Lydia; Calandrelli, Matías; Lanas Zanetti, Fernando Tomas; Manfredi, Jose Anibal; Olivera, Héctor; Seron, Pamela; Ponzo, Jacqueline; He, Jiang
Abstract : Introduction: Cardiovascular diseases (CVD) are increasing throughout the world and cause 16.7 million deaths each year, 80% of which occur in low and middle income countries. In Argentina, Chile and Uruguay, the available data on cardiovascular risk factors come predominantly from cross-sectional studies that are principally based on self-report or studies conducted with small convenience samples. The CESCAS I study will generate reliable estimates of the prevalence and distribution of and secular trends in CVD and its risk factors in this region. Methods and analysis: CESCAS I is an observational prospective cohort study with a multistage probabilistic sample of 8000 participants aged 35–74 years from four mid-sized cities representing the Southern Cone of Latin America: Bariloche and Marcos Paz in Argentina, Temuco in Chile and Pando-Barros Blancos in Uruguay. In the first phase, baseline data regarding exposure to risk factors and prevalence of CVD will be collected in two stages: (1) in homes and (2) in health centres. Information will be gathered on medical history, risk factors, lifestyles and health utilisation through specific questionnaires, physical measurements, an ECG and an overnight, fasting blood sample to measure levels of serum lipids, glucose and creatinine. In the second phase, annual follow-up data will be obtained on the incidence rate of CVD events and the association between exposure and events. Ethics and dissemination: The protocol has obtained formal ethics approval from institutional review boards in Argentina, Chile, Uruguay and the USA. The lack of follow-up studies has prevented Argentina, Chile and Uruguay from implementing risk factor stratification and management strategies at a population level. However, the CESCAS I study data will help the development of public health strategies based on primary care intervention, thus helping to improve cardiovascular health in this region.